Cell surface receptors for herpes simplex virus are heparan sulfate proteoglycans (The Rockefeller University Press, 1992)
The role of cell surface heparan sulfate in herpes simplex virus (HSV) infection was investigated using CHO cell mutants defective in various aspects of glycosaminoglycan synthesis. Binding of radiolabeled virus to the cells and infection were assessed in mutant and wild-type cells. Virus bound efficiently to wild-type cells and initiated an abortive infection in which immediate-early or alpha viral genes were expressed, despite limited production of late viral proteins and progeny virus. Binding of virus to heparan sulfate-deficient mutant cells was severely impaired and mutant cells were resistant to HSV infection. Intermediate levels of binding and infection were observed for a CHO cell mutant that produced undersulfated heparan sulfate. These results show that heparan sulfate moieties of cell surface proteoglycans serve as receptors for HSV.